(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Gastritis, peptic ulcers, and gastric cancer are the most common disorders and the leading cause of death worldwide. Helicobacter pylori is a bacterium that has been related to stomach inflammation, Peptic Ulcer, as well as gastric cancer. The current study sought to identify natural inhibitors of the Crystal Structure of Carboxyspermidine Dehydrogenase in a complex with Nicotinamide adenine dinucleotide phosphate (PDB ID: 8H52). Natural inhibitors appear to be a potential treatment strategy for inhibiting H. Pylori. 1102 Bioactive compounds from significant traditional medicinal herbs were selected. The initial selection results were based on the physicochemical, absorption, distribution, metabolism, excretion, and toxicity (ADMET) traits and other drug-like traits. Binding energy calculations and interaction analysis were applied to identify safe and efficient results. 17 Bioactive compounds were found with binding affinities between -7.8 Kcal/mol and -9.9 Kcal/mol. Among 17; curcumin pyrazole, scoparol, tryptanthrin and 4-O-methylcatechin displayed effective interactions with docking scores of -9.9 Kcal/mol, -9.6 Kcal/mol, 9.5 Kcal/mol, and -9.5 Kcal/mol respectively compared to the control drug Omeprazole (-8.8 Kcal/mol). Molecular dynamic simulation revealed that 4'-O-methyl catechin is stable inside the binding pocket 8H52 and can be used as a potential therapeutic agent to cure intestinal disorders.